Design and testing of McMurray Inverter for Emergency Loads - Mohibullah; Norman, Mariun; Noor Izzri, Abdul Wahab; Ong, Yoke Teng (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 18th - 19th May 2005 at Putra Palace Hotel, Kangar.